2023
DOI: 10.2967/jnumed.122.265364
|View full text |Cite
|
Sign up to set email alerts
|

Human Epidermal Growth Factor Receptor 2–Targeting [68Ga]Ga-ABY-025 PET/CT Predicts Early Metabolic Response in Metastatic Breast Cancer

Abstract: Visual Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…However, this threshold was not confirmed in a more recent trial, and their results showed a lack of correlation of [ 68 Ga]GaABY-025 with immunohistochemistry data, similar to our current findings. [ 68 Ga]GaABY-025 uptake did, however, predict metabolic response to HER2-targeted therapy in patients with metastatic breast carcinoma with 56% sensitivity and 66% specificity ( 37 ). [ 89 Zr]Zr-trastuzumab PET/CT is able to distinguish HER2-positive from HER2-negative disease but suffers from the tracer’s long biologic half-life, necessitating scanning after several days ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, this threshold was not confirmed in a more recent trial, and their results showed a lack of correlation of [ 68 Ga]GaABY-025 with immunohistochemistry data, similar to our current findings. [ 68 Ga]GaABY-025 uptake did, however, predict metabolic response to HER2-targeted therapy in patients with metastatic breast carcinoma with 56% sensitivity and 66% specificity ( 37 ). [ 89 Zr]Zr-trastuzumab PET/CT is able to distinguish HER2-positive from HER2-negative disease but suffers from the tracer’s long biologic half-life, necessitating scanning after several days ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is due to the fact that small proteins tend to be abundantly deposited in the kidney, which may be associated with the renal elimination and reabsorption of the Affibody molecules [ 25 , 26 , 27 , 28 ]. Despite these tendencies, we expect that NIR-PIT using the EGFR Affibody–IR700Dye conjugate is fully applicable for clinical use because Affibody and IR700Dye are already used clinically [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…These are essential advantages of Affibody molecules compared with monoclonal antibodies. Affibody molecules have been successfully evaluated as promising targeting agents for both preclinical (Orlova et al 2006 ; Strand et al 2014 ; Rosestedt et al 2015 ; Garousi et al 2016 ; Andersson et al 2016 ; Oroujeni et al 2018 , 2021 ; Liu et al 2022 ) and clinical (Sörensen et al 2014 , 2016 ; Alhuseinalkhudhur et al 2023 ; Bragina et al 2023 ) imaging of different molecular targets. Safety of this drug class has furthermore been demonstrated clinically with up to three years chronic patient dosing, suggesting viability for repeated administrations (Klint et al 2023 ).…”
Section: Introductionmentioning
confidence: 99%